Dynamics of a motor vehicle taking into consideration the interaction of wheels and road pavement surface - Olegas Prentkovskis; Marijonas BogdeviÄius (Transport, 2002)
The authors of this article focus on the simulation of the motor vehicle on a certain road and propose their specific solution of this problem. A mathematical model of the system â€œmotor vehicle - roadâ€ is presented. The motor vehicle is simulated by concentrated masses interconnected by elastic and dissipative links. The presented model of the motor vehicle evaluates the movement of the motor vehicle body in space; the movement and turning of front and rear suspensions with respect to the body; the interaction of the wheel with the road pavement surface; the blocking of the wheel; the changing cohesive forces which influence the motor vehicle. The investigated road pavement surface is simulated by triangular finite elements, the certain height of road pavement surface roughness and the cohesion coefficients of road pavement surface and the motor vehicle wheel in the longitudinal and transverse directions of the wheel are selected in each finite element nodal point. The presented results illustrate: the motor vehicle movement trajectories braking at various initial conditions and on a certain pavement surface of the road section under investigation and the motor vehicle driving on the speed reduction bump (â€œsleeping policemanâ€).